KAJIAN LITERATUR: GAMBARAN AWAL TINGKAT DEPRESI DENGAN IDE BUNUH DIRI PADA REMAJA SMP-MAHASISWA - Wazna Layalia Alyan; Linda Widyastuti; Priscalina Dea Sukmana (IBERS : Jurnal Pendidikan Indonesia Bermutu, 2023)
Adolescence is a turbulent time full of contradictions and mood swings, physical, emotional, social, and cognitive changes. These changes can cause various problems, one of which is depression. Depression is a mental disorder that makes individuals feel depressed and hopeless. One of the impacts of depression is the desire for suicide as an attempt to solve the problem. Suicide can be defined as the act of taking one's own life by assuming that the problem will be solved when the individual commits suicide. The purpose of this study was to obtain an overview of the level of depression with suicidal ideation in adolescents. This study used a qualitative method with a literature review approach of six scientific articles. The results of this study indicate that there is a relationship between the level of depression and suicidal ideation in adolescents, because the higher the level of depression, the higher the suicidal ideation and vice versa, the lower the level of depression, the lower the suicidal ideation. It is hoped that adolescents will be better able to recognize themselves so that they can better control their emotions so that they can overcome every problem and avoid negative behavior that can cause feelings of depression and have an impact on the presence of suicidal ideation.